IMPLEMENTATION OF A STRATEGY BASED ON GAMIFICATION IN THE FD5094 MATHEMATICS CURRICULUM COURSE AT THE UNIVERSITY OF COSTA RICA - Campos, Camilo (2026)
This paper aims to share an experience involving the application of gamification in the course FD5094: Curriculum in Mathematics at the University of Costa Rica, as part of a teacher training program in Mathematics Education. The strategy was implemented during a class presentation using a digital board inspired by the video game Mario Party, designed in PowerPoint. Through challenges, coins, and items, the activity sought to encourage active participation and understanding of the course content. However, several difficulties emerged due to unclear rules and participants’ unfamiliarity with the game dynamics. Based on this experience, reflections are presented on the importance of proper planning, the alignment between game elements and learning objectives, and the potential of gamification as a tool to enhance motivation and engagement in university learning environments.